2009
DOI: 10.1016/j.juro.2008.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Attenuates Renal Injury in an Experimental Model of Rat Unilateral Ureteral Obstruction via Anti-Inflammatory and Anti-Apoptotic Effects

Abstract: Erythropoietin exerts renoprotective effects in an experimental unilateral ureteral obstruction rat model via anti-apoptotic and anti-inflammatory actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…In this study, renal IRI increased the levels of Bcl-2, Bax and cleaved Caspase3, while NADPH treatment reduced these phenotypes. A similar observation was found in that Bcl-2 and Bax were mainly localized in renal tubular cells, and that levels of Bcl-2 and Bax were remarkably increased in IRI kidneys compared with the sham group [42]. However, Na et al observed that Bax expression was significantly elevated, and that Bcl-2 expression was decreased in IR kidney [24].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, renal IRI increased the levels of Bcl-2, Bax and cleaved Caspase3, while NADPH treatment reduced these phenotypes. A similar observation was found in that Bcl-2 and Bax were mainly localized in renal tubular cells, and that levels of Bcl-2 and Bax were remarkably increased in IRI kidneys compared with the sham group [42]. However, Na et al observed that Bax expression was significantly elevated, and that Bcl-2 expression was decreased in IR kidney [24].…”
Section: Discussionsupporting
confidence: 67%
“…The plasma was separated by centrifugation (10 min, 4°C), and aliquots were snap-frozen in liquid nitrogen and stored at -70°C. Tissues were prepared as previously described [24]. Briefly, the left kidney was excised immediately after sacrifice and cut into three coronal sections.…”
Section: Blood and Tissue Preparationmentioning
confidence: 99%
“…Immunohistochemistry Immunohistochemistry was performed as described previously [24]. Paraffin wax-embedded tissues were cut into 4 µm sections, mounted on glass slides, and stained using indirect immunoperoxidase.…”
Section: Light Microscopymentioning
confidence: 99%
“…22,23 The third possible mechanism is the inhibitory effect of EPO on inflammation and fibrosis. Attenuation of interstitial inflammation and fibrosis by EPO therapy has been reported in the models of chronic cyclosporine nephropathy, 24 ureteral obstruction, [25][26][27] and Thy-1 glomerulonephritis. 28 In addition, other mechanisms have been suggested to be involved in the direct renoprotective effect of EPO.…”
Section: Discussionmentioning
confidence: 93%